Types of Adjacency Pairs on The Six Minutes English Program in BBC Learning English - Wice Marsella; Azwandi Azwandi; Arasuli Arasuli (UNIB Press, 2023)
This research aimed to describe the Adjacency Pairs phenomena in the BBC Learning English, comprising two adjacency pairs aspects: The most frequently types of adjacency pairs used by the participants and the most frequently initiators of the first part in adjacency pairs. This research used quantitative descriptive research. The object of this research was one video contained (5 parts), the topic